Quantifying noise in survey expectations - Artūras Juodis; Simas Kučinskas (Quantitative Economics, 2023)
Expectations affect economic decisions, and inaccurate expectations are costly. Expectations can be wrong due to either bias (systematic mistakes) or noise (unsystematic mistakes). We develop a framework for quantifying the level of noise in survey expectations. The method is based on the insight that theoretical models of expectation formation predict a factor structure for individual expectations. Using data from professional forecasters, we find that the magnitude of noise is large (10%-30% of forecast MSE) and comparable to bias. We illustrate how our estimates can be applied to calibrate models with incomplete information and bound the effects of measurement error.
Keywords: C53; D83; E70; G40; 330; Expectation formation; factor models; measurement error; noise; panel data; subjective expectations